Serotonin Toxicity: Associated Agents and Clinical Characteristics. Issue 6 (November 2019) - Moss, Michael J.; Hendrickson, Robert G.
Abstract: Background: Serotonin toxicity is a common cause of drug-induced altered mental status. However, data on the causes of serotonin toxicity, symptomatology, complications, and rate of antidotal treatment are limited. Methods: This study evaluated cases of serotonin toxicity in the ToxIC registry, an international database of prospectively collected cases seen by medical toxicologists. Serotonin toxicity was diagnosed by bedside evaluation of medical toxicology specialists and explicit criteria were not used. The database was searched for "serotonin syndrome" between January 1, 2010, and December 31, 2016. Results: There were 1010 cases included. Females made up 608 (60%) cases. Ages are as follows: younger than 2 years (3, 0.3%), 2 to 6 years (8, 0.8%), 7 to 12 years (9, 0.9%), 13 to 18 years (276, 27.3%), 19 to 65 years (675, 67%), older than 66 years (33, 3.4%), unknown (6, 0.6%). Reasons for encounter: intentional (768, 76%), adverse drug event/reaction (127, 12.6%), unintentional (66, 6%), and unknown (55, 5.4%). Signs/symptoms: hyperreflexia/clonus/myoclonus (601, 59.5%), agitation (337, 33.4%), tachycardia (256, 25.3%), rigidity (140, 13.9%), seizures (139, 13.7%), and hyperthermia (29, 2.9%). Complications: rhabdomyolysis (97, 9.7%), dysrhythmias (8, 0.8%), and death (1, 0.1%). Treatments: benzodiazepines 67% (677/1010), cyproheptadine 15.1% (153/1010). There were 192 different xenobiotics reported with 2046 total exposures. Antidepressants were most common (915, 44.7%) with bupropion the most frequent overall (147, 7.2%). Common non-antidepressants were dextromethorphan (95, 6.9%), lamotrigine (64, 3.1%), and tramadol (60, 2.9%). Discussion: Serotonin toxicity most often occurred in adult patients with intentional overdose. Antidepressants were the most common agents of toxicity. Interestingly, bupropion, a norepinephrine/dopamine reuptake inhibitor, was the most frequently mentioned xenobiotic. Though often cited as a potential antidote, only 15% of patients received cyproheptadine. Severe toxicity was rare. A single death was reported.